Sex hormone mediated change on flexion reflex - Soedirdjo, Subaryani D. H.; Chung, Yu-Chen; Dhaher, Yasin Y. (Frontiers in Neuroscience, 2023)
It has been shown that estrogen and progesterone receptors are expressed in the spinal cord; therefore, fluctuation in their concentrations may affect the spinal network and modulate the control of movement. Herein, we assessed the neuro-modulatory effect of sex hormones on the polysynaptic spinal network by using a flexion reflex network as a model system. Twenty-four healthy eumenorrheic women (age 21–37 years) were tested every other day for one menstrual cycle. Serum estradiol and progesterone were acquired at the time of testing. The flexion reflex of the tibialis anterior was elicited by sending an innocuous electrical stimulus directly to the posterior tibial nerve or plantar cutaneous afferent. Analyses were performed for each menstrual cycle phase: the follicular phase and the luteal phase. Increases in estradiol or progesterone concentrations were not associated with reflex duration or root mean squared (RMS) amplitude in either the follicular or luteal phases. In the luteal phase, an increase in the estradiol concentration was associated with a longer latency of the reflex (b = 0.23, p = 0.038). The estradiol × progesterone interaction was found towards significance (b = −0.017, p = 0.081). These results highlight the potential synergistic effect of estradiol and progesterone and may provide indirect confirmatory evidence of the observed modulatory effect.